How Can Aerial Imagery and Vegetation Indices Algorithms Be Used for Monitoring CropsThrough Geotagged System? A Review - Vikneswaran Jeya Kumaran; Nur Adibah Mohidem; Nik Norasma Che’Ya; Wan Fazilah Wan Ilahi; Jasmin Arif Shah; Norhakim Yusof (HH Publisher, 2024)
Vol. 4 No. 1